The C-terminal region of yeast ubiquitin–protein ligase Not4 mediates its cellular localization and stress response. Issue 15 (2nd August 2021) - Palermo, Vanessa; Stirpe, Mariarita; Bianchi, Michele Maria; Rinaldi, Teresa; Cirigliano, Angela; Ragnini-Wilson, Antonella; Falcone, Claudio; Mazzoni, Cristina
ABSTRACT: Transient modification of the environment involves the expression of specific genes and degradation of mRNAs and proteins. How these events are linked is poorly understood. CCR4-NOT is an evolutionary conserved complex involved in transcription initiation and mRNA degradation. In this paper, we report that the yeast Not4 localizes in cytoplasmic foci after cellular stress. We focused our attention on the functional characterization of the C-terminus of the Not4 protein. Molecular dissection of this region indicates that the removal of the last 120 amino acids, does not affect protein localization and function, in that the protein is still able to suppress the thermosensitivity observed in the not4Δ mutant. In addition, such shortened form of Not4, as well its absence, increases the transcription of stress-responsive genes conferring to the cell high resistance to the oxidative stress. On the contrary, the last C-terminal 211 amino acids are required for proper Not4 localization at cytoplasmic foci after stress. This truncated version of Not4 fails to increase the transcription of the stress genes, is more stable and seems to be toxic to cells undergoing oxidative stress. Abstract : The C-terminal region of Not4 ubiquitin ligase mediates the formation of cytoplasmic foci after stress. In addition, this region contains positive and negative elements that influence cell resistance to hydrogen peroxide.